Analisis Implementasi Budaya Sadar Arsip di Direktorat Jenderal Pembinaan Hubungan Industrial dan Jaminan Sosial Tenaga Kerja Kementerian Ketenakerjaan RI - Vinda Selfiana,; Roni Faslah,; Rizki Firdausi R, (Jurnal Bintang Pendidikan Indonesia, 2025)
This research was conducted at the Directorate General of Industrial Relations and Labor Security of the Ministry of Manpower of the Republic of Indonesia which discusses the accumulation of archives in the room. The research uses a qualitative descriptive approach, namely by analyzing the problems found. Primary data in this study were obtained by conducting observations, interviews, and documentation, while secondary data were obtained through books, previous research, and articles related to the research. The purpose of this research is to find out how the implementation of an archive-conscious culture, how the impact of an archive-conscious culture and also how to overcome the obstacles that occur in archive shrinkage. According to the views of employees, archive-conscious culture has been socialized and the accumulation of archives is slowly decreasing, there is a positive impact where the Directorate General of PHI JSK already has an archival SOP which makes archive management more controlled, efforts to optimize archive shrinkage through technical guidance or socialization related to shrinkage so that archives can be managed more effectively.